Antiepileptic Drug of Levetiracetam Decreases Centrotemporal Spike-Associated Activation in Rolandic Epilepsy - Zhang, Qirui; Yang, Fang; Hu, Zheng; Xu, Qiang; Bernhardt, Boris C.; Quan, Wei; Li, Qian; Zhang, Zhiqiang; Lu, Guangming (Frontiers in Neuroscience, 2018)
To study the modulation effects of levetiracetam on fMRI activation /deactivation patterns associated with centrotemporal spikes (CTS) in rolandic epilepsy. Forty patients with rolandic epilepsy, including levetiracetam-medicated patients (n=20) and drug-naive patients (n=20), were studied. Single and sequential hemodynamic response functions-based EEG-fMRI analysis was performed to detect dynamic activation/deactivation associating to CTS. Comparisons of spatiotemporal features of activation/deactivation were performed between two groups. Both groups (CTS were detected in 12 cases of levetiracetam medicated group, and 11 cases of drug-naive group) showed CTS-associated activation in the rolandic cortex, while activation strength, time-to-peak delay, and overall activation were diminished in the levetiracetam-medicated group. Moreover, the drug-naive group showed deactivation in the regions engaged in higher cognition networks comparing with levetiracetam medicated group. Levetiracetam inhibits CTS-associated activation intensity and alters the temporal pattern of this activation in the epileptogenic regions, and it also affects the brain deactivation related to higher cognition networks. The findings shed lights on the pharmocological mechanism of levetiracetam therapy on rolandic epilepsy.